Monitoring diversity in genome-wide association studies requires measuring and reporting on immigration-related factors - Tu, Yao; Fernandez-Rhodes, Lindsay (Frontiers in Genetics, 2026)
Genome-wide association studies (GWAS) have made remarkable progress to date in deciphering the genetic foundations of complex traits, yet persistent gaps remain in how sample heterogeneity is measured and reported. Current practices typically emphasize diversity by broad ancestry categories or stratification by country of recruitment, but these dimensions alone fail to capture the immigration-related factors that contribute to the genetic or environmental origins of heterogeneity. We argue that incorporating variables, such as country of origin, in descriptions and analyses provides essential context for interpreting genetic associations, particularly in increasingly multi-population and trans-national GWAS samples. We highlight how neglected these variables are in the literature using the GWAS Catalog. We provide suggestions for reporting on these data in future studies. By advocating for a more comprehensive view of diversity in GWAS, we aim to address the under-representation of immigrants in GWAS and thereby strengthen the validity and interpretability of future genomic studies.